Bringing up the boss practical lessons for new managers - Rachel Pacheco (Dallas, TX Matt Holt Books, an imprint of BenBella Books, Inc., 2021)
New start-ups come on the scene filled with incredible young people. These start-ups grow, the team expands, and those young people all of a sudden have the responsibility of a team under them. As "managers", they are expected - often without any direction or manager role models - to know how to develop, coach, structure work, review, and set expectations for a whole bunch of new, incredible young people.
Includes bibliographical references (pages 265-281).
Keywords: Supervision of employees